2000
DOI: 10.1046/j.1464-410x.2000.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of cholinergic detrusor excitation in a pig model of bladder hypocompliance

Abstract: Objective To investigate the role of cholinergic excitation in mediating changes in detrusor compliance (manifested on conventional cystometry as an incremental rise in detrusor pressure as bladder volume increases) under conditions of propofol-sedation in the pig. Materials and methods Consecutive cystometrograms (CMGs) were obtained from eight female Large White pigs at a bladder ®lling rate of 50 mL/min. The ®rst CMG was obtained while the pig was awake and unsedated. Two subsequent CMGs were obtained after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…This intravenous (IV) anesthetic is short-acting and the depth of the anesthesia is easily adjusted by adjusting the rate of infusion. In addition, the animals recover quickly after the anesthesia is [33]. The cat's bladder was catheterized with a double-lumen catheter with one lumen opening into a side port (Braintree Scientific model DLR-4, 1.25 mm OD).…”
Section: Measurement Of Bladder Pressure and Urethral Sphincter Tonementioning
confidence: 99%
“…This intravenous (IV) anesthetic is short-acting and the depth of the anesthesia is easily adjusted by adjusting the rate of infusion. In addition, the animals recover quickly after the anesthesia is [33]. The cat's bladder was catheterized with a double-lumen catheter with one lumen opening into a side port (Braintree Scientific model DLR-4, 1.25 mm OD).…”
Section: Measurement Of Bladder Pressure and Urethral Sphincter Tonementioning
confidence: 99%
“…However, when spinal cord connections to the bladder were maintained, TTX enhanced the activity (14,15). This suggests that spontaneous activity might have an origin within the bladder (11) but that the spinal cord exerts an inhibitory control.…”
mentioning
confidence: 99%
“…Another study in larger pigs with a weight that ranged from 49 to 65 kg (mean weight not reported) using a ¢lling rate more similar to ours of 50 ml/min found an average cystometric capacity of 700 ml (10.8^14.3 ml/ kg) [Mills et al, 2000]. Whether the di¡erence in capacity between normal pigs and the MPTP-pigs receiving deep brain stimulation is related to the stimulation or the MPTP-intoxication is a matter of speculation.…”
Section: The Storage Functionmentioning
confidence: 52%